Transisi Guru Ke Pensiun: Mengarungi Perubahan dalam Adaptasi Pasca-Karir (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Retirement is an important event that marks the change from adult life to old life. One of the things that need to be prepared in facing retirement is to reduce the workload as retirement approaches. The sociological transition theory developed by William Bridges, known as the "Bridges Transition Model," underscores the importance of understanding and managing change as a transitional process involving three main stages: suffix, neutral, and beginning, The theory of social capital proposed by Pierre Bourdieu can provide relevant understanding related to the phenomenon of teacher adaptation in retirement. This theory emphasizes the importance of social networks and relationships in the lives of individuals, and considers social capital as a valuable resource. The study used a qualitative approach, which showed that teachers who had strong social networks during their careers were more likely to have social support and resources that could help them in post-retirement adaptation. Teachers who have strong social networks during their careers are better able to cope with the challenges of post-retirement adaptation. On the other hand, the results also show that teachers who lack social capital or have a more limited social network will have difficulty in post-retirement adaptation.